Multiscale and Uniform Liquid Metal Thin‐Film Patterning Based on Soft Lithography for 3D Heterogeneous Integrated Soft Microsystems: Additive Stamping and Subtractive Reverse Stamping. Issue 7 (17th May 2018) - Kim, Min‐gu; Kim, Choongsoon; Alrowais, Hommood; Brand, Oliver
Abstract: The use of intrinsically soft conductors, such as gallium‐based liquid metal (eutectic gallium–indium alloy, EGaIn), has enabled bioinspired and skin‐like soft electronics. Thereby, creating patterned, smooth, and uniform EGaIn thin films with high resolution and size scalability is one of the primary technical hurdles. Soft lithography using wetting/nonwetting surface modifications and 3D heterogeneous integration can address current EGaIn patterning challenges. This paper demonstrates multiscale and uniform EGaIn thin‐film patterning by utilizing an additive stamping process for large‐scale (mm–cm) soft electronics and a subtractive reverse stamping process for microscale (µm–mm) soft electronics. While EGaIn patterning based on stamping is regarded as the least reliable patterning technique, this paper highlights multiscale and uniform thin‐film patterning by stamping at room temperature and under atmospheric pressure utilizing proper chemical/physical surface modification to obtain selective nonwetting or uniform wetting properties. By combining structures fabricated using these additive and subtractive stamping techniques with 3D heterogeneous integration, functional soft microsystems are demonstrated: i) a soft LC (inductor‐capacitor) sensing platform with high areal capacitance, ii) a fingertip‐mountable biological sensing platform, and iii) soft heaters with localized and distributed heating capability. The demonstrated fabrication and integration approaches enable high‐density and multifunctional soft microsystems for versatile sensing applications. Abstract : This paper presents multiscale and uniform EGaIn thin‐film patterning by utilizing an additive stamping process for large‐scale (mm–cm) soft electronics and a subtractive reverse stamping process for microscale (µm–mm) soft electronics. By combining structures fabricated using these additive and subtractive stamping techniques with 3D heterogeneous integration, functional soft microsystems are demonstrated for physical, chemical, and biological applications.